2006
DOI: 10.1002/arp.297
|View full text |Cite
|
Sign up to set email alerts
|

Beneath the sand—remote sensing, archaeology, aggregates and sustainability: a case study from Heslerton, the Vale of Pickering, North Yorkshire, UK

Abstract: TheVale of Pickering, inYorkshire hasbeenthe setting forone of thelargest archaeologicalresearch projects in Europe for more than 30 years.The accrued data includes over 1000 ha of fluxgate gradiometer measurements that can be interpreted with reference to 200 ha of subsurface mapping, 25 years of aerial photographic survey, two large-area multispectral and vertical photographic surveys, a Laser Imaging Detection and Ranging (LIDAR) survey and area excavations in excess of 22 ha. Crucially, this multifaceted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Early studies utilising multispectral sensors for archaeology found that by creating false colour composite (FCC) images utilising different wavelength bands, particularly around the red‐edge (~700 nm) and near infrared (NIR) (~700–1100 nm) wavelengths, crop marks could be visualised more clearly than through a true colour image, occasionally revealing previously unidentified features (Cavalli, Colosi, Palombo, Pignatti, & Poscolieri, ; Donoghue & Shennan, ; Powlesland et al, ). More recent studies have looked at how wider ranges of spectral information captured by both airborne and spaceborne multispectral sensors may be most effectively, and subjectively, exploited for archaeological prospection particularly in comparison to aerial photography (Agapiou et al, ; Bennett et al, ; Doneus et al, ; Traviglia, ; Verhoeven & Sevara, ).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies utilising multispectral sensors for archaeology found that by creating false colour composite (FCC) images utilising different wavelength bands, particularly around the red‐edge (~700 nm) and near infrared (NIR) (~700–1100 nm) wavelengths, crop marks could be visualised more clearly than through a true colour image, occasionally revealing previously unidentified features (Cavalli, Colosi, Palombo, Pignatti, & Poscolieri, ; Donoghue & Shennan, ; Powlesland et al, ). More recent studies have looked at how wider ranges of spectral information captured by both airborne and spaceborne multispectral sensors may be most effectively, and subjectively, exploited for archaeological prospection particularly in comparison to aerial photography (Agapiou et al, ; Bennett et al, ; Doneus et al, ; Traviglia, ; Verhoeven & Sevara, ).…”
Section: Introductionmentioning
confidence: 99%
“…The archaeological applications of airborne lidar topographic data are now well known. As well as geoarchaeological mapping and prospection (Brunning and Far‐Cox, 2005; Challis, 2005, 2006; Carey et al ., 2006; Challis et al ., 2006; Jones et al ., 2007), published applications include over‐arching landscape studies (Barnes, 2003; Bewley et al ., 2005; Bofinger et al ., 2006; Shell and Roughley, 2004; Powlesland et al ., 2006), investigation of the potential for lidar to detect upstanding archaeological remains beneath the vegetation canopy (Deveraux et al ., 2005; Risbol et al ., 2006; Sittler and Schellberg, 2006; Crow et al ., 2007; Doneus et al ., 2008) and studies of the uses of lidar to contribute to the compilation and refinement of records of the historic environment (Holden et al ., 2002; Bewley, 2003; Crutchley, 2006; Challis et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Light detecting and ranging, or lidar, uses aircraft laser sweeps to create remarkably detailed models of ground topography that can in turn be used for a range of purposes such as survey and archaeological prospection (Bewley et al 2005;Carey et al 2006;Challis 2006;Challis and Howard 2006;Crow et al 2007;Crutchley 2006;Devereux et al 2005;Harmon et al 2006;Kvamme et al 2006b;Powlesland et al 2006;Rowlands and Sarris 2007). Of the myriad of new laser mapping available, lidar is perhaps one of the most useful for archaeology since recording landscape topography is a regular part of surveying.…”
Section: Laser Mapping: Range Finders 3d Scanners and Lidarmentioning
confidence: 98%